The resilient city and adapting to the health emergency: Towards sustainable university mobility - Pirlone, Francesca; Spadaro, Ilenia (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The concept of a resilient city is an increasingly critical one. Resilience represents the ability of an urban system to adapt to an external event. In the past, urban resilience was mainly addressed to natural rather than anthropic risks. Considering the Covid-19 pandemic emergency, the relationship between urban resilience and anthropic risk, especially health risk, has inevitably distorted the “normality” to which we were accustomed. The emergency has had significant long-term effects on the times, uses and organization of cities. Adaptability requires the synergic work of all actors who live or work in a city. This mobility-focused research aims to highlight the importance of the Quadruple Helix principle by analysing the specific measures that each actor -Public Authorities, Research, Enterprises and Citizens- can implement to reduce health risk. The paper outlines the contribution of the University of Genoa within the confines of a ministerial project to promote sustainable mobility for students, when travelling between home and university, using prizes/incentives. This good practice will play an increasingly important role in the return to normality.